Coupling Lipid Labeling and Click Chemistry Enables Isolation of Extracellular Vesicles for Noninvasive Detection of Oncogenic Gene Alterations (Adv. Sci. 14/2022). Issue 14 (16th May 2022) - Sun, Na; Tran, Benjamin V.; Peng, Zishan; Wang, Jing; Zhang, Ceng; Yang, Peng; Zhang, Tiffany X.; Widjaja, Josephine; Zhang, Ryan Y.; Xia, Wenxi; Keir, Alexandra; She, Jia‐Wei; et al.
Abstract : Extracellular Vesicle In article number 2105853 by Renjun Pei, Shaohua Lu, Hsian‐Rong Tseng, Yazhen Zhu, and co‐workers, an efficient, convenient, and rapid extracellular vesicle (EV) enrichment platform called EV Click Beads is developed by combining lipid labelling and click chemistry‐based capturing. EV Click Beads provides a non‐invasive diagnostic solution for detection of disease status and monitoring treatment response for cancer patients, including Ewing sarcoma, the second most common type of bone cancer in children.